Molecular profiling of signaling pathways involved in chicken ovarian follicle development by transcriptome sequencing - Wadood, Armughan Ahmed; Bordbar, Farhad; Safdar, Muhammad; Zhang, Xiquan (Frontiers in Veterinary Science, 2026)
Ovarian follicle development in chickens is a dynamic and closely controlled biological process crucial to avian reproduction. Each stage of folliculogenesis is characterized by distinct morphological and molecular alterations, regulated by complex signaling pathways. This study employed transcriptome sequencing to investigate the molecular landscape that governs the transition from primordial (PR) to primary (PM), small white (SW), and small yellow (SY) follicles. We found stage-specific activation of critical signaling pathways involved in follicle growth and development using thorough differential gene expression and pathway enrichment analyses. Our findings showed that the PI3K/AKT/mTOR signaling pathway was highly elevated throughout the shift from PR to PM follicles, highlighting its importance in beginning cellular proliferation and protein synthesis. During development, the Wnt signaling system was regulated from the PM to the SW follicles. This included β-catenin-mediated transcriptional regulation, granulosa cell proliferation, and communication between oocytes and somatic cells. Furthermore, the transition from SW to SY follicles was characterized by a significant increase in glycerophospholipid metabolism, emphasizing the metabolic reprogramming required for rapid cellular development and membrane production. The combination of transcriptome data and route mapping provides essential insights into the molecular mechanisms underpinning folliculogenesis in chickens. The signaling pathways revealed the representative stage-specific regulatory networks required for optimal follicle development. These findings enhance our understanding of avian ovarian biology and suggest potential targets for improving reproductive efficiency in chickens.